Allah Harapan Kita di Masa Krisis Pandemi Covid-19 - Kristoforus Bala (Sekolah Tinggi Widya Sasana, 2021)
The current Covid-19 pandemic has led to existential crises throughout the whole world. It has affected many aspects of human life. It has caused fear, anxiety, despair and even death of millions of people. This article focuses on the importance and meaningfulness of hope in God in the midst of the Covid-19 crisis. In Christian theology, hope is one of the theological virtues. It has become increasingly important and urgent for Christians and theologians to reflect on hope in God as the ultimate source of hope for humankind in such a time like this. In the midst of the widespread of various misinterpretations of the Covid-19 pandemic, Christians and theologians are called to contribute their theological reflections for the betterment of individuals, societies and humanity at large especially in coping with and responding to the pandemic crisis. The method applied in this article is qualitative, i.e. by studying in depth biblical sources, magisterial documents and Catholic teaching on theme of hope in God as a theological virtue and other sources that are related to the topic of the Covid-19 pandemic.